2019
DOI: 10.1021/acsami.9b11703
|View full text |Cite
|
Sign up to set email alerts
|

Nanoporous Ni3P Evolutionarily Structured onto a Ni Foam for Highly Selective Hydrogenation of Dimethyl Oxalate to Methyl Glycolate

Abstract: Methyl glycolate (MG) is a versatile platform molecule to produce numerous important chemicals and materials, especially new-generation biocompatible and biodegradable poly­(glycolic acid). In principle, it can be massively produced from syngas (CO + H2) via gas-phase hydrogenation of CO-derived dimethyl oxalate (DMO), but the groundbreaking catalyst represents a grand challenge. Here, we report the discovery of a Ni-foam-structured nanoporous Ni3P catalyst, evolutionarily transformed from a Ni2P/Ni-foam engin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 51 publications
2
31
0
Order By: Relevance
“…S7, ESI †), which is higher than that of the Cu-based catalyst (49.0 kJ mol À1 ) 45 but lower than that of the reported Ni 3 P/SiO 2 catalyst (76.0 kJ mol À1 ). 37 What's more, the E a of the MG-to-EG process for the Co 8 P/SiO 2 catalyst was 91.5 kJ mol À1 (Fig. S7, ESI †), much higher than that of the Cu-based catalyst (54.0 kJ mol À1 ) 45 which can explain the higher MG selectivity of the P-modified Co-based catalyst than the Cu-based catalysts.…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…S7, ESI †), which is higher than that of the Cu-based catalyst (49.0 kJ mol À1 ) 45 but lower than that of the reported Ni 3 P/SiO 2 catalyst (76.0 kJ mol À1 ). 37 What's more, the E a of the MG-to-EG process for the Co 8 P/SiO 2 catalyst was 91.5 kJ mol À1 (Fig. S7, ESI †), much higher than that of the Cu-based catalyst (54.0 kJ mol À1 ) 45 which can explain the higher MG selectivity of the P-modified Co-based catalyst than the Cu-based catalysts.…”
mentioning
confidence: 93%
“…The catalyst displayed an unexceptionable stability with 100% conversion of DMO and 76% selectivity to MG during the 3600 h time-on-stream. Furthermore, Lu et al 37 have found that Ni 3 P/Ni-foam can provide 495% selectivity at nearly 100% conversion in the DMO to MG reaction and they also proposed that Ni 3 P with a higher surface electron density showed higher catalyst performance than the Ni 2 P catalyst. Nowadays, transition metal phosphides (TMPs) with unique and desirable physicochemical properties have attracted much attention.…”
mentioning
confidence: 99%
“…Methyl glycolate (MG), containing both hydroxyl and ester groups, is an important fine chemical [ 1 , 2 , 3 ]. As it has similar chemical properties to alcohol and ester, MG can undergo various reactions such as carbonylation, hydrolyzation, and oxidation [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…As it has similar chemical properties to alcohol and ester, MG can undergo various reactions such as carbonylation, hydrolyzation, and oxidation [ 4 , 5 ]. Many traditional synthetic technologies, such as the carboxylation of formaldehyde and condensation of methyl formate with formaldehyde [ 2 , 6 , 7 ], have been applied for the synthesis of MG. However, disadvantages such as environmental pollution, harsh production process, and low stability of catalyst are obvious [ 2 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation